Bryophytes of the Western-Zerafshan Ridge (Uzbekistan) - Zhalov , Kholmurod; Farrux, Abdirasulov (Plant Science Today, 2022)
A historical overview of bryological studies in Uzbekistan and a list of 80 known species of mosses from the Republic of Uzbekistan, compiled from well-known publications, collections stored in the herbaria of Samarkand State University and the Beijing Botanical Institute of the Chinese Academy of Sciences, and ourdata are presented. Hygroamblystegium tenax Hedw., Lewinskya affinis (Schrad. ex Brid F.Lara) Garilleti & Goffinet, Pseudoleskeella papillosa (Lindb.) Kindb, Encalypta trachymitria Ripart and Orthotrichum hallii Sullivant & Lesquereux are reported for the first time in Uzbekistan.